Elodea Nuttallii (Planch.) St. John (Hydrocharitaceae) - A New Angiospermic Record for Bangladesh - Nawrin, Kazi Sadia; Alfasane , Md Almujaddade; Hassan , Md Abul (Bangladesh Journal of Plant Taxonomy, 2024)
Elodea nuttallii (Planch.) St. John has been explained as a new report from Bangladesh. The taxonomic description including flowering, fruiting, ecology and distribution of the species are elaborated here. Bangladesh J. Plant Taxon. 31(1): 51-55, 2024 (June)